أنماط التفاعل الاسري و علاقتها بمستوى الطموح لدى الابناء المتمدرسين السنة الثالثة ثانوي بثانوية الصادق طالبي بالاغواط - نسرين ميلودي; عائشة مشراوي; محمد بوفاتح (My University, 2023)
This study aimed to identify the patterns of family interaction and their relationship to the level of ambition among the sons enrolled in the third year secondary at Al-Sadeq Talibi Secondary School. We used the descriptive approach and applied the level of ambition scale consisting of 62 (by its owner Muhammad Boufateh 2005) and the scale of family interaction patterns consisting of 26 items from the construction of the two students. The sample was randomly selected and consisted of 51 male and female students enrolled in the third year secondary at Al-Sadeq Talibi Secondary School during the academic year 2022 / 2023. After the statistical treatment, the study was divided into the following results: There is no relationship between family interaction patterns and level of ambition among sons enrolled in the third year secondary at Al-Sadeq Talibi Secondary School. 1. There are no gender differences in family interaction patterns. 2. There are no gender differences in level of ambition. 3. There are no differences in family interaction patterns due to academic specialization. 4. There are no differences in level of ambition due to academic specialization Keywords: Family interaction Level of ambition Sons